The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3390/ijms21093384
|View full text |Cite
|
Sign up to set email alerts
|

A Data-Driven Review of the Genetic Factors of Pregnancy Complications

Abstract: Over the recent years, many advances have been made in the research of the genetic factors of pregnancy complications. In this work, we use publicly available data repositories, such as the National Human Genome Research Institute GWAS Catalog, HuGE Navigator, and the UK Biobank genetic and phenotypic dataset to gain insights into molecular pathways and individual genes behind a set of pregnancy-related traits, including the most studied ones—preeclampsia, gestational diabetes, preterm birth, and placental abr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 54 publications
1
19
0
2
Order By: Relevance
“…This is the largest GWAS of PND conducted to date; however, still far below the sample size that identified genetic variants associated with MDD, it failed to identify any genome‐wide significant SNPs. Although the most significant SNP did not meet genome‐wide significance, its location within the KAZN gene may be of relevance to the etiology of PND as this gene has previously been associated with post‐traumatic stress disorder (Nievergelt et al, 2019), endometriosis (Christofolini et al, 2019), complications of pregnancy (Barbitoff et al, 2020), albumin‐to‐creatinine‐ratio (Haplotype Reference Consortium, 2016) (which has also been associated with depression; Martens et al, 2018), and a reproductive subtype of polycystic ovary syndrome (Dapas et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This is the largest GWAS of PND conducted to date; however, still far below the sample size that identified genetic variants associated with MDD, it failed to identify any genome‐wide significant SNPs. Although the most significant SNP did not meet genome‐wide significance, its location within the KAZN gene may be of relevance to the etiology of PND as this gene has previously been associated with post‐traumatic stress disorder (Nievergelt et al, 2019), endometriosis (Christofolini et al, 2019), complications of pregnancy (Barbitoff et al, 2020), albumin‐to‐creatinine‐ratio (Haplotype Reference Consortium, 2016) (which has also been associated with depression; Martens et al, 2018), and a reproductive subtype of polycystic ovary syndrome (Dapas et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although extensive studies have been conducted, the etiology of PE remains unknown. However, multiple factors have been implicated, including endothelial 4 , 5 , immunological 6 , and genetic factors 7 , 8 . It has been suggested that an inadequate maternal immunological response to the semiallogenic fetus and consequently abnormal placentation could cause PE.…”
Section: Introductionmentioning
confidence: 99%
“…Many PE-associated genes and pathways have been reported [ 52 , 53 ], but it is unlikely that the etiology of PE would be explained by any one of these factors; it is highly probable that multiple associated genes act together. Expanding our knowledge of the inter-connectivity of PE-associated genes in functional pathways is thus crucial to fully elucidate the mechanisms underlying PE.…”
Section: Discussionmentioning
confidence: 99%